Targeting the hypoxic tumour phenotype with T-cell immunotherapy - Chong, T (2004)
The hypoxic tumour phenotype is a widespread phenomenon in cancers that correlates with malignant behaviour and poor clinical outcomes. The induced expression of hypoxia-regulated genes through post-translational stabilization of hypoxia-inducible factor (HIF), represent a novel class of over expressed tumour antigens that may bear relevance for specific T cell immunity. To assess whether hypoxia inducible proteins can elicit specific T cell responses in vivo, experiments were carried out using complementary models. Initially, specific T cell responses to a hypoxia-regulated antigen |3 galactosidase (pgal) in a mouse melanoma model were investigated. The responses correlated to hypoxia-induced expression of (3gal in vitro, and resulted in anti-tumour effects in vivo. Next, the utility of human carbonic anhydrase 9 (CA9) as a tumour antigen was explored. In particular, renal cell carcinomas (RCC) which constitutively express CA9 as a result of HIF stabilization through loss of von-Hippel Lindau (VHL) tumour suppressor gene, were targeted. Since the HLA-A2 restricted peptide CA9254 . 2 62 was reported to be immunogenic and endogenously presented in human cells, peptide specific T cell responses were induced in vivo using HLA-A2 transgenic mice, and monitored with novel CA9-specific tetramers. Subsequently, CA9 specific T cell responses in HLA-A2 healthy donors and RCC patients were generated in vitro which recognized exogenous but not endogenously presented peptide as a result of low avidity interactions, or failure of correct processing and presentation by antigen presenting cells. To assess whether anti-angiogenic therapy can be combined with vaccination strategies, the combination of anti-angiogenic and specific T cell immunotherapy was explored using a novel 'metronomic dosing' regime of cytotoxic agent cyclophosphamide. A synergistic anti-tumour effect in a murine melanoma model was demonstrated, while sparing a population of memory T cells that were subsequently capable of re-expansion. Finally, a novel iron chelator desferri-exochelin was found to induce HIF and downstream targets, suggesting that specific T cell immunotherapy against hypoxiaregulated targets may be enhanced through chemical means. Additionally, desferriexochelin was anti-angiogenic in vitro, and inhibited tumour cell proliferation through HIF independent pathways.